Quantitative aspects of cortisol feedback on the secretion of ACTH in dogs. - Windle, Wayne J. (University of Ottawa (Canada), 1975)
Seven male mongrel dogs of 8.3--13.1 kg. were bilaterally adrenalectomized and maintained for one week on replacement therapy, discontinued early enough to eliminate feedback effects of glucocorticoids by experiment time. Each dog, under light Nembutal anesthesia, received two stepwise primed constant infusions of cortisol (i.v.), each lasting 90 minutes. 23 venous blood samples were withdrawn for determination of plasma ACTH concentrations by adrenal cell suspension bioassay and 25 samples for plasma cortisol determination, at various times before, during and after the cortisol infusions. ACTH secretion rates were calculated using previously determined ACTH clearance and distribution volume characteristics. As a mean of 6 animals, the cortisol concentration plateaux, which averaged 4.59 +/- 0.57 and 6.49 +/- 0.92 mug/100 ml., caused suppression of ACTH secretion (expressed as percentage of pre-period secretion rates) from 0% before cortisol to 65.05% suppression during plateau # 1 and to 95.3% suppression during plateau # 2. 70 minutes after the cessation of cortisol infusion the plasma cortisol had fallen to 1.95 +/- 0.43 mug/100 ml. with an associated 69.6% suppression of ACTH secretion rate. The suppression, associated with the two infusion periods and the delay associated with the recovery in the post-infusion period, suggests a delayed feedback of the order of 1 hour. The infused cortisol resulted in low physiological plasma levels of cortisol which had the following characteristics in these adrenalectomized dogs: metabolic clearance rates of 12.8 and 17.4 ml/kg. min associated, respectively, with mean plasma cortisol concentrations of 4.27 and 6.23 mug/100 ml. (MCR increasing with increasing cortisol concentration) and an apparent distribution volume of about 40% V (distribution volume not correlated with plasma cortisol levels). Also, results on an as yet incomplete series of stress (histamine, anoxia) experiments showing suppression of stress induced ACTH secretion by low physiological plasma concentrations of cortisol, are included in an appendix.
Keywords: Biology, Animal Physiology.